Permasalahan Implementasi UU 21 Tahun 2000 Tentang Serikat Pekerja/Serikat Buruh - Al Ayubbi, Syaefuddin Ahrom; Maryani, Maryani (Sahabat Akademia Group, 2024)
This research aims to analyze the problems of implementing Law 21 of 2000 concerning Trade Unions. This research is field research with descriptive qualitative methods. Data was collected through interview techniques with informants from trade union members. Field findings highlight several crucial aspects, including problems with the implementation of Law 21/2000, restrictions on members, and the lack of accommodation of regulations for informal workers and migrant workers. Protection of informal workers requires special regulations, while labor inspection needs to be improved to enforce the law and maintain harmonious industrial relations. Implementation of the layoff mechanism from Law 13/2003 requires stronger law enforcement, while employment social security programs need to be optimized, especially for informal workers who lack literacy. Challenges are also faced by women in the labor market, creating gender inequality that requires a struggle to achieve equal positions. This research highlights the significant challenges that need to be addressed to improve the state of industrial relations, worker protection, and gender equality in Indonesia.